EVALUASI SISTEM REKAPITULASI HONORARIUM TENAGA PENDIDIK BERDASARKAN PROGRAM KEGIATAN MAHASISWA DI UNIVERSITAS BINA DARMA - Naura Dewi Mutiara; Andrian Noviardy; Poppy Indriani (CV. ADIBA AISHA AMIRA, 2026)
This study aims to evaluate the honorarium recapitulation system for teaching staff based on student activity programs at Bina Darma University. The study was motivated by the increasing complexity of managing student and teaching staff data as various programs under the Kampus Berdampak initiative continue to expand. Data that remain scattered across multiple files, lack integration, and are processed manually have resulted in a recapitulation process that is less effective and prone to administrative errors. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation during an internship at the Kampus Berdampak Service Center of Bina Darma University. The findings indicate that the existing system has supported administrative processes in determining the number of students supervised by teaching staff, which serves as the basis for honorarium calculation. However, several challenges were identified, including the absence of centralized data management, inconsistencies in data formats, manually conducted data grouping processes, and the lack of a comprehensive data verification mechanism. The system evaluation highlights the need for a more integrated data management approach through data standardization, database consolidation, and the implementation of systematic verification procedures. These improvements are expected to enhance the effectiveness, efficiency, and accuracy of the teaching staff honorarium recapitulation process while supporting the quality of higher education administrative management.